Will China’s Brand of Stakeholder Capitalism Sustain Development in the Next 20 Years? - Ronald W. Anderson (Financial and Economic Review)
Since 1978, China has developed strongly using a particular form of capitalism that has relied on close relations between private enterprise and the state, and the continuing presence of state-owned enterprises, both centrally and at local levels. This model has been criticised as being responsible for the rapid rise of debt since 2010, and more recently for the slowdown of growth. I assess the challenges to China’s stated growth ambitions, emphasising the demographic factors that vary across regions. Using examples at the regional and local levels, I illustrate the workings of this system and highlight the challenges for adapting it to support China’s growth ambitions for the coming decades.The conclusion is that China’s public-sector development can no longer be financed principally through land sales, and Chinese savers will need to shift away from real estate and redirect their investments toward equities and other capital-market vehicles.